Cost and Time Optimization Analysis using the Time Cost Trade Off Method - Dwiyana, Putri Ayu; Siti Agmaliza; Rajiman (Journal of Civil Engineering and Planning (JCEP), 2025)
The implementation of construction projects often faces delays that are difficult to avoid, as experienced in the construction of the City X Hospital Building, where there was a discrepancy between the initial plan and actual field implementation, resulting in a two-week delay in weekly progress. This study aims to analyze time and cost efficiency and compare the effectiveness of alternatives between extending working hours and adding labor using the Time Cost Trade Off method. This research is comparative, comparing the total cost and duration of the project for both acceleration alternatives. The total project cost under normal conditions was recorded at IDR 7,289,386,643.45 with a duration of 86 days until the completion of the third floor. The analysis shows that extending working hours by 1 to 4 hours resulted in costs of IDR 14,584,817,481; IDR 21,871,659,072; IDR 28,672,701,971; and IDR 34,564,808,294, with cost efficiency of –100.08%, –200.05%, –293.35%, and –374.18%, respectively. The project duration was reduced to 64, 50, 41, and 36 days, with time efficiency of 26%, 42%, 53%, and 58%. Meanwhile, the alternative of adding labor resulted in a total cost of IDR 13,660,989,499 with a cost efficiency of –87.41% and a project duration of 64 days (26% time efficiency). Based on these results, both extending working hours by one hour and adding labor showed the most efficient outcomes, but overall, adding labor was considered more optimal as it achieved the same acceleration with the lowest total cost.